Entanglement of Several Classical and Dynamic Estimates with Unified Approach on Time Scales (Journal of Nonlinear Modeling and Analysis, 2025)
In this research article, we present several generalizations of Qi’sinequality on time scales. We establish dynamic versions of Callebaut’s inequality and Cauchy-Schwarz’s inequality on time scales. To establish ourresults, we apply the diamond-alpha integral and the time scale $∆$ or $∇$-Riemann-Liouville type fractional integrals. Our findings unify and extenddiscrete, continuous and quantum analogues.